1996
DOI: 10.1073/pnas.93.22.12611
|View full text |Cite
|
Sign up to set email alerts
|

A neurotensin antagonist, SR 48692, inhibits colonic responses to immobilization stress in rats.

Abstract: We previously reported that short-term immobilization stress of rats causes increased colonic mucin release, goblet cell depletion, prostaglandin E2 secretion, and colonic mast cell activation, as well as increased colonic motility. The purpose of this study was to investigate whether neurotensin (NT), a peptide expressed in both brain and digestive tract, participates in these responses. Rats were pretreated with SR 48692 (1 mg/kg, i.p.), an NT antagonist, 15 min before immobilization (30 min). The administra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
44
0
3

Year Published

1999
1999
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(52 citation statements)
references
References 37 publications
5
44
0
3
Order By: Relevance
“…These results are in agreement with those of recent studies showing that sulfated oligosaccharides on MUC5B function as adhesion molecules for H. pylori (42,43). The findings of our study resemble the results of animal studies investigating the effects of acute stressors (ie, water immersion and restraint stress) on the activity of secretory cells in the colon, stomach, and nasopharynx (63)(64)(65)(66)(67)(68)(69)(70)(71). These studies demonstrated robust effects of acute stress on mucin release, synthesis, and glycosylation (a process in which carbohydrate structures on proteins are formed).…”
Section: J a Bosch Et Alsupporting
confidence: 77%
“…These results are in agreement with those of recent studies showing that sulfated oligosaccharides on MUC5B function as adhesion molecules for H. pylori (42,43). The findings of our study resemble the results of animal studies investigating the effects of acute stressors (ie, water immersion and restraint stress) on the activity of secretory cells in the colon, stomach, and nasopharynx (63)(64)(65)(66)(67)(68)(69)(70)(71). These studies demonstrated robust effects of acute stress on mucin release, synthesis, and glycosylation (a process in which carbohydrate structures on proteins are formed).…”
Section: J a Bosch Et Alsupporting
confidence: 77%
“…NTR1-mRNA and NT binding sites have been identified in the brain (15), small and large intestine of animals and humans (13,15), human colonic epithelial cell lines (16,17), human blood mononuclear cells (11), and endothelial cells (18). Recently, we demonstrated the presence of NTR1 mRNA in the rat colonic mucosa, including colonic epithelial cells (19). We also showed that administration of the specific NT receptor nonpeptide antagonist SR-48,692 to rats attenuated colonic mucin secretion and mast cell activation following immobilization stress, indicating a critical role for NT in stress-related colonic responses (19).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies underline the importance of NTR1 in several intestinal pathologic conditions. For example, administration of the specific NTR1 antagonist SR 48692 to rats inhibits colonic mucin and prostaglandin E2 secretion and mast cell activation in response to immobilization stress (18). NTR1 antagonism also reduces colonic secretion and inflammation mediated by Clostridium difficile toxin A (19), and increased NTR1 expression is evident in the colonic mucosa during the course of acute colitis mediated by this potent enterotoxin (19).…”
mentioning
confidence: 99%